Evaluation of atmospheric deposition and patterns of polycyclic aromatic hydrocarbons in façades of historic monuments of Oporto (Portugal) - Slezakova, Klara (2014)
Atmospheric pollution by motor vehicles is considered a relevant source of damage to architectural heritage. Thus the aim of this work was to assess the atmospheric depositions and patterns of polycyclic aromatic hydrocarbons (PAHs) in façades of historical monuments. Eighteen PAHs (16 PAHs considered by US EPA as priority pollutants, dibenzo[a,l]pyrene and benzo[j]fluoranthene) were determined in thin black layers collected from façades of two historical monuments: Hospital Santo António and Lapa Church (Oporto, Portugal). Scanning electron microscopy (SEM) was used for morphological and elemental characterisation of thin black layers; PAHs were quantified by microwave-assisted extraction combined with liquid chromatography (MAE-LC). The thickness of thin black layers were 80–110 μm and they contained significant levels of iron, sulfur, calcium and phosphorus. Total concentrations of 18 PAHs ranged from 7.74 to 147.92 ng/g (mean of 45.52 ng/g) in thin black layers of Hospital Santo António, giving a range three times lower than at Lapa Church (5.44– 429.26 ng/g; mean of 110.25 ng/g); four to six rings compounds accounted at both monuments approximately for 80–85% of ΣPAHs. The diagnostic ratios showed that traffic emissions were significant source of PAHs in thin black layers. Composition profiles of PAHs in thin black layers of both monuments were similar to those of ambient air, thus showing that air pollution has a significant impact on the conditions and stone decay of historical building façades. The obtained results confirm that historical monuments in urban areas act as passive repositories for air pollutants present in the surrounding atmosphere.